Speaking Truth to Power: Core Principles for Advancing International Journalism Education - V. Pavlik, John; أبو السعد, عدنان; Laufer, Peter (ALBAHITH ALALAMI, 2022)
A confluence of forces has brought journalism and journalism education to a precipice. The rise of fascism, the advance of digital technology, and the erosion of the economic foundation of news media are disrupting journalism and mass communication (JMC) around the world. Combined with the increasingly globalized nature of journalism and media, these forces are posing extraordinary challenges to and opportunities for journalism and media education. This essay outlines 10 core principles to guide and reinvigorate international JMC education. We offer a concluding principle for JMC education as a foundation for the general education of college students.